Evaluation of Investors' Perception towards Mutual Funds Investment (Trinity Journal of Management, IT & Media (TJMITM), 2018)
The aim of the study is to examine investors' perception towards  mutual funds in India and also to identify attributes that are crucial  for taking investment decisions in mutual funds. Stratified random  sampling has been used for collection of responses through  structured questionnaire. Factor analysis was used for data  analysis using SPSS to find out factors that have impact on  investors' perception. During the factor analysis, all the eighteen  items were reduced to eight factors explaining 65.18% of  variance. The factors were selected on the basis of eigenvalues  and only eight factors having eigenvalue greater than one were  retained to interpret the results. Eight factors were found having  maximum (13.56%) for first factor (funds information related  attributes) and lowest (5.85%) for the eighth factor (funds capital  appreciations attribute). The model was tested using reproduced  correlations matrix and found fit.
Keywords: Investors; Mutual funds; Attributes; Perception